The effect of varying the duration of the butane/air pretreatment on the morphology and reactivity of (VO)2P2O7 catalysts - Waugh, K.C; Taufiq-Yap, Y.-H (Elsevier, 2003)
Three vanadium pyrophosphate catalysts have been prepared by calcining vanadium hydrogen phosphate hemihydrate (VOHPO4·0.5H2O), prepared in an organic medium, for different lengths of time (40, 100 and 132h) in a n-butane (0.75%)/air mixture at 673K. The catalysts were designated VPO40, VPO100 and VPO132. Increasing the duration of reaction with n-butane/air mixture led to an increase in the total surface area from 21.3 (VPO40) to 24.9 m2g-1 (VPO100) and 27 m2g-1 (VPO132). It also led to the complete removal of the VOPO4 phase from catalysts VPO100 and VPO132, this VOPO4 phase having been seen as a minor component of catalyst VPO40. Scanning electron microscopy showed that longer periods of pretreatment in the n-butane/air mixture produced catalysts with increasing amounts of a characteristic rosette-type of agglomerate. Increasing the duration of the butane/air pretreatment at 673 K resulted in a lowering in the amount of oxygen desorbed on temperature programming, indicating that the butane/air pretreatment was effectively reducing. However, and apparently paradoxically, increasing the duration of the butane/air pretreatment resulted in an increase in the amount of oxygen removed from the catalysts by temperature programmed reduction in H2, rising from 11 monolayers for VPO40 to 14 monolayers for VPO100 and to 15 monolayers for VPO132. All three catalysts showed a reduction peak with a maximum temperature of ∼1000 K for the removal of 11 monolayers of oxygen, while catalysts VPO100 and VPO132 showed a second reduction peak at ∼1100 K for the removal of an additional three (VPO100) and four monolayers (VPO132) of oxygen.